2020
DOI: 10.18295/squmj.2020.20.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Plagiarism Perceptions and Attitudes Among Medical Students in Saudi Arabia

Abstract: Objectives: This study aimed to determine attitudes towards and perceptions of plagiarism among medical students in Saudi Arabia. Methods: This cross-sectional, multicentre study was conducted between April and May 2018 and involved medical students enrolled in three medical schools in Riyadh, Saudi Arabia. The previously validated Attitude Towards Plagiarism questionnaire was used to evaluate approval (i.e. a positive attitude) and disapproval of plagiarism (i.e. a negative attitude) among medical students. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
(22 reference statements)
2
9
1
Order By: Relevance
“…The study indicated that students are needed to be exposed to ethical aspects of academic writing at the same time they are exposed to format of academic writing. similar to existing studies such as by Alhadlaq et al (2020), the study showed that students must be guided to produce academic writing with proper format as well to use information ethically and develop references using a proper style in the academic writing.…”
Section: Discussionsupporting
confidence: 68%
“…The study indicated that students are needed to be exposed to ethical aspects of academic writing at the same time they are exposed to format of academic writing. similar to existing studies such as by Alhadlaq et al (2020), the study showed that students must be guided to produce academic writing with proper format as well to use information ethically and develop references using a proper style in the academic writing.…”
Section: Discussionsupporting
confidence: 68%
“…These findings are similar to those of a study conducted in Croatia that found that the majority of pharmacy students felt the same way [ 13 ]. However, many studies carried out among medical students reported that, in most cases, plagiarism is due to a lack of instruction in research methods and reference practices [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The implication is that management students can easily access this information from the internet, making plagiarism a significant threat to the intellectual integrity of this group. Although the concept of plagiarism has been examined in prior studies, discipline specific enquiries; including veterinary studies in India (Singh, 2017), medical studies in Saudi Arabia (Alhadlaq, Dahmash, & Alshomer, 2020); medical students in Pakistan (Javaeed, Khan, Khan, & Ghauri, 2019); tourism and hospitality (Goh, 2015); nursing (Goodwin & McCarthy, 2020); pharmacy (Mohamed et al, 2018) and business science (Quispe, Núñez, Arias, Chávez, & Cara, 2019) have been carried out in different contexts. However, there are limited studies on the perceptions of student plagiarism among the management sub-discipline of Transport, Logistics and Supply Chain Management.…”
Section: Literature Reviewmentioning
confidence: 99%